Adoption of e‑learning by pre‑university students following the COVID‑19 pandemic: an analysis based on the unifed theory of acceptance and use of technology (UTAUT) - Noor Saadiah, Mohd Ali; Fauzi, Muhammad Ashraf; Saidin, Nurhafizah; Md Nor, Nurur Raudzah; Ismail, Nur Farrah Syazwanie; Aling, Noor Asiah (2024)
The COVID-19 pandemic has had immense consequences for education systems worldwide. Institutions had to quickly switch to remote teaching and learning (RTL) as an alternative delivery mode. The study presented here investigated the implementation of an e-learning system for Malaysian pre-university students. The study employed the unifed theory of acceptance and use of technology (UTAUT) to evaluate 503 pre-university students’ adoption of e-learning across various states in Malaysia. The analysis was performed through partial least square structural equation modelling (PLS-SEM). The fndings show that all UTAUT variables were signifcant except for efort expectancy and facilitating condition. Platform availability was found to be highly signifcant to the intention to engage in e-learning. Despite the existence of a large body of research on the experiences of students in higher education during the COVID-19 pandemic, there have been few studies of pre-university students. The authors also discuss theoretical and managerial implication